Polycystic Ovary Syndrome (PCOS) in Juvenile and Adult Type 1 Diabetes in a German/Austrian Cohort - Reinauer, Christina; Bollow, Esther; Fröhlich-Reiterer, Elke; Laubner, Katharina; Bergis, Dominik; Schöfl, Christof; Kempe, Hans-Peter; Hummel, Michael; Hennes, Pia; Gollisch, Katja; Haberland, Holger; Datz, Nicolin; Meissner, Thomas; Holl, Reinhard W. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Context While an association between PCOS and type 2 diabetes is well established, to date there have been few data on clinical care of type 1 diabetes (T1D) patients with PCOS.Objective The aim of our study was to characterize T1D patients with the comorbidity of PCOS within the DPV cohort with regard to diabetes phenotype, therapy and metabolic control.Design and Setting Clinical data from the prospective German/Austrian DPV cohort on patients with T1D and documented PCOS (n=76) were compared to female T1D controls (n=32,566) in reproductive age.Results The age at T1D manifestation in PCOS patients was later than in the control group (14.9±8.2 vs. 11.8±7.0 years, p<0.001). PCOS patients had higher BMI-SDS (0.92±0.11 vs. 0.38±0.01, p<0.001), metformin and oral contraceptives were used more frequently (p<0.001). A1c levels were significantly lower (7.92 +/− 0.23% vs. 8.43±0.01%, p<0.05) despite of lower insulin requirements (0.76±0.04 IU/kg/d vs. 0.84±0.00 IU/kg/d, p<0.05). In the PCOS group, higher rates of dyslipidemia (63.4 vs. 48.7%, p =0.032) and thyroid disorders (42.2% vs. 21.2%, p<0.001) were present.Discussion While patients with T1D and comorbid PCOS showed features of a “type 1.5 diabetes” phenotype, insulin requirements per kg body weight were not higher and metabolic control was better, which could be explained only partially by additional metformin therapy. A more precise genetic and metabolic characterisation of these patients is needed to answer open questions on the underlying autoimmune process and residual ß-cell function.